Оптимізація компоновки пакувальних технологічних ліній - Кривопляс-Володіна, Людмила Олександрівна; Токарчук, Сергій Володимирович; Валіулін, Геннадій Раіфович (My University, 2016)
Стаття присвячена вирішенню важливої проблеми щодо компонування автоматизованих пакувальних технологічних ліній. Проектування та компонування пакувальних технологічних ліній є найбільш складним і визначальним етапом забезпечення їх ефективності. Авторами розглянуто основні аспекти та переваги використання математичного моделювання при проектуванні пакувальних технологічних ліній. Article is devoted to the solution of an important problem concerning configuration of the automated packaging processing lines. Configuration optimization — an important factor of the solution of tasks power — and resource-saving, the mistakes made at this design stage lead to difficult consequences as from the point of view of excessive costs of energy, materials and products, and from the point of view of losses of appliances. Authors have considered the main aspects and benefits of use of mathematical modeling when designing packaging processing lines. The algorithm of optimization is presented in the form of four-level hierarchical structure. The task of modeling and designing of the formalized volume and spatial technological system is solved.
Keywords: оптимізація; проектування; пакування; математична модель; ефективність; optimization; design; packing; mathematical model; efficiency; кафедра мехатроніки та пакувальної техніки